Mild water deficit during maturity reduces cracking rate of greenhouse muskmelon while improving fruit quality - Qimin Xue; Hao Li; Taisheng Du (Agricultural Water Management)
Fruit cracking is frequent in fleshy fruits and is closely related to unreasonable irrigation, affecting fruit yield and quality at harvest and therefore sales. However, it remains to be demonstrated whether there are reasonable deficit irrigation (DI) practices that could reduce fruit cracking while ensuring that yield is not reduced and fruit quality is improved. Three-season (spring 2021, spring 2022 and summer 2022) deficit irrigation experiments were conducted to investigated the responses of greenhouse muskmelons (Cucumis melo var. chinensis) in terms of plants water status, yield, irrigation water productivity (IWP), fruit cracking rate, output value and fruit quality. Results showed that cracked fruit rate was significantly positive with irrigation amount at fruit maturity stage (stage M). Furthermore, it was related with stem water potential at midday and transpiration just at stage M, not flowering-swelling stage (stage F). Although yield and IWP were not significantly affected under mild DI applied at stage M, cracked fruit rate was significantly decreased by 73 %, resulting in the highest output value. The application of DI during both stage F and M had a negative impact on fruit size, fresh weight and dry matter weight, but had a remarkable positive effect on the accumulation of soluble solids such as sugars. The comprehensive quality score based on principal component analysis and membership function method revealed that severe DI applied at entire reproductive period had optimal comprehensive quality score. Entropy-TOPSIS result indicated that mild deficit irrigation applied at stage M was a reasonable strategy for greenhouse substrate cultivation of muskmelon. This study provides a reasonable irrigation regime, which not only helps to improve fruit quality and ensure yield at harvest, but also reduces economic losses due to lower fruit cracking and opens up new prospects for horticultural production.